Effects of Chopping on Utilization of Sorghum Stover by Nubian Goats - Mohammed Hamed, Asma Himmed; Elimam, Mohamed Elamin (Pakistan Journal of Nutrition, 2009)
Effects of chopping sorghum stover (Tabat variety) on Dry Matter Intake (DMI), apparent digestibility and body weight changes in Nubian goats were studied in the Gezira, Sudan. The chemical composition of the stover (%) was 96.78 ±0.83, 1.43 ±0.02, 4.65 ±0.39, 42.98 ±0.01, 9.99 ±0.89 and 40.96 ±1.24 for DM, EE, CP, CF, ash and NFE, respectively. Dry matter intake on different basis was higher for the chopped stover and the effect was significant (p<0.05) as g/d (606 for the long and 687 for the short). Chopping decreased losses in BW, but not significantly. It was (kg/week) 0.616 for the long and 0.366 for the short. Chopping increased nutrients apparent digestibilities and the effect was significant (p<0.05), except for CF and EE. They were 55.20, 59.11, 18.60 and 41.78 and 67.89 for DM, OM, CP, EE and CF, respectively for the long and 65.87, 68.15, 45.28, 53.90 and 72.47, respectively for the short.